1991
DOI: 10.1002/jobm.3620310202
|View full text |Cite
|
Sign up to set email alerts
|

Phyllosphere and phylloplane fungi of qat in Sana'a, Yemen Arab Republic

Abstract: Eighty six species belonging to thirty one genera were collected from the qat phyllosphere (30 genera and 78 species) and phylloplane (20 genera and 64 species) of 24 varieties tested. In the phyllosphere the most frequent genera were Cladosporium, Aspergillus and Alternaria followed by Penicillium, Drechslera, Fusarium, Curvularia, Phoma and Chaetomium. From the preceding genera the most prevalent species were C. herbarum, C. macrocarpum, A. niger, A. flavus, A. alternata, A. phragmospora, P. citrinum, P. not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…KAMAL and SINGH 1970, MOUBASHER et al 1971, MISHRA and DICKINSON 1981, ANDREWS et al 1987, ANDREWS and HARRIS 2000. Cladosporium sphaerospermum, a very frequent fungal specie in our study, has been found less frequently in the phylloplane of other plants (DOMSCH et al 1980, ALHUBAISHI andABDEL-KADER 1991). This fungus has been more related with leaf litter substrates (DOMSCH et al 1980), cotton debris (SALEEM et al 1975 and decaying stems of Urtica dioica Lin.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…KAMAL and SINGH 1970, MOUBASHER et al 1971, MISHRA and DICKINSON 1981, ANDREWS et al 1987, ANDREWS and HARRIS 2000. Cladosporium sphaerospermum, a very frequent fungal specie in our study, has been found less frequently in the phylloplane of other plants (DOMSCH et al 1980, ALHUBAISHI andABDEL-KADER 1991). This fungus has been more related with leaf litter substrates (DOMSCH et al 1980), cotton debris (SALEEM et al 1975 and decaying stems of Urtica dioica Lin.…”
Section: Resultsmentioning
confidence: 84%
“…This anatomical property, and particularly the shape of the wax crystals, together with the trichomes, will determine leaf wettability (FOKKEMA 1991). In general, the species richness in phylloplane samples from a Mediterranean ecosystem was smaller when compared with other studies of fungal communities from several ecosystems, specially, when compared with both tropical and temperate habitats (DICKINSON 1976, BREEZE and DIX 1981, ALHUBAISHI and ABDEL-KADER 1991, BILL and POLISHOOK 1994. When compared with Antarctic habitats (MÖLER and DREYFUSS 1996), extreme alpine environment (PETROVIC et al 2000) and samples of seaweeds from Iberian coasts (GENILLOUD et al 1994), Mediterranean ecosystem showed more species diversity.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Records of smaller Ascomycetes and their anamorphs have been published by COOKE (1882 and in BALFOUR 1888), FORBES (1903), KAMAL et al (1983KAMAL et al ( , 1984, SATTAR & HAIT-HAMI (1986), SATTAR & BAHAMISH (1990), ALHUBAISHI & ABDEL-KADER (1991), YU et al (1993, EL-SAID (1995), EL-SAID & ABDEL-HAFEZ (1994), KUATE (1998).…”
Section: Larger Ascomycetesmentioning
confidence: 97%